Found in Translation: Applying Lessons from Model Systems to Strigolactone Signaling in Parasitic Plants. Issue 7 (July 2017) - Lumba, Shelley; Subha, Asrinus; McCourt, Peter
Abstract : Strigolactones (SLs) are small molecules that act as endogenous hormones to regulate plant development as well as exogenous cues that help parasitic plants to infect their hosts. Given that parasitic plants are experimentally challenging systems, researchers are using two approaches to understand how they respond to host-derived SLs. The first involves extrapolating information on SLs from model genetic systems to dissect their roles in parasitic plants. The second uses chemicals to probe SL signaling directly in the parasite Striga hermonthica . These approaches indicate that parasitic plants have co-opted a family of α/β hydrolases to perceive SLs. The importance of this genetic and chemical information cannot be overstated since parasitic plant infestations are major obstacles to food security in the developing world. Trends: A nuclear hormone receptor system is involved in SL signaling in model plants. The SL receptor in model plants is a α/β hydrolase that metabolizes the hormone. Parasitic plants have co-opted a collection of α/β hydrolases related to model plant SLs receptors to perceive host SLs. Chemical probes have been useful in functionally understanding the roles of parasitic plant receptors in germination.